BEBAN KERJA PENGARUHNYA TERHADAP BURNOUT DI PT. BANK MANDIRI (PERSERO), TBK KANTOR CABANG DENPASAR GAJAH MADA DENGAN WORK FAMILY CONFLICT SEBAGAI VARIABEL MODERASI - wayan arya paramarta; ayu asih riska dewi (Forum Manajemen STIMI Handayani Denpasar, 2021)
This research was conducted based on the gap in the results of previous research (research gap) and the difference in focus of discussion on workload and work family conflict on burnout. In addition, there are also research problems regarding the high employee absenteeism at PT. Bank Mandiri (Persero), Tbk Denpasar Gajah Mada Branch Office. This study aims to examine and analyze the effect of workload on burnout with work family conflict as a moderating variable. This research was conducted at PT. Bank Mandiri (Persero), Tbk Denpasar Gajah Mada Branch Office with a population of 62 and the sample of this study amounted to 58 respondents. All data obtained from the questionnaire distribution were suitable for use, then analyzed using Smart PLS 3.0. The results showed that (1) workload had a positive and significant effect on burnout, (2) work family conflict had a positive and significant effect on burnout and (3) work family conflict was able to positively moderate the effect of workload on burnout. The implication of this research is that the workload can be increased by paying attention to the indicators of effort, where PT. Bank Mandiri (Persero), Tbk Denpasar Gajah Mada Branch is expected to be able to overcome or provide solutions in reducing the sense of physical and mental fatigue of employees which can result in unstable employee performance.